The night manager [videorecording (Blu-Ray)] - Hiddleston, Tom; Laurie, Hugh, 1959-; Colman, Olivia; Hollander, Tom, 1967-; Bullock, Rob; Farr, David, 1969-; Bier, Susanne, 1960-; Le Carré, John, 1931-2020 (Sony Pictures Home Entertainment, 2016)
Jonathan Pine is working as the night manager of a Cairo hotel. He gets involved with a local woman who is the girlfriend of a local gangster. Through her relationship with the gangster she has acquired information linking illegal international arms sales with an English billionaire.